2016
DOI: 10.3892/or.2016.4845
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nuclear ribonucleoprotein K is overexpressed and associated with poor prognosis in gastric cancer

Abstract: Heterogeneous nuclear ribonucleoprotein K (hnRNP K) is one of the major pre-mRNA-binding proteins, that is involved in translational modifications. In our previous studies, we found that hnRNP K is associated with human gastric cancer. The protein levels of hnRNP K were detected in cell lines and tissue microarrays. The correlation between hnRNP K expression and patient survival rate was evaluated by Kaplan-Meier survival analysis. In addition, we also detected hnRNP K expression in preoperative and postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Gastric cancer (GC) is a highly malignant tumor with complicated pathogenesis. While progress has been achieved in understanding the aetiology and risk factor of GC, there has been little improvement in GC survival rates (17,18). The keystones to improving health outcomes remain the early diagnosis and efficacious treatment (19).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer (GC) is a highly malignant tumor with complicated pathogenesis. While progress has been achieved in understanding the aetiology and risk factor of GC, there has been little improvement in GC survival rates (17,18). The keystones to improving health outcomes remain the early diagnosis and efficacious treatment (19).…”
Section: Discussionmentioning
confidence: 99%
“…Many other RBPs also exhibit changed expression in GC tissues. The hnRNP‐A1, ‐A2/B1, ‐C, ‐F, ‐K, polypyrimidine tract‐binding protein (PTBP)‐1, ‐3, poly r(C) binding protein 2, IMP‐3, Musashi‐1, and non‐POU domain containing octamer binding protein (NONO) were upregulated (C. Chen et al, ; Huang et al, ; Jing et al, ; P. T. Lee et al, ; D. Li et al, ; Park et al, ; Shou et al, ; Sugiyama et al, ; S. H. Xu et al, ; R. Yang et al, ; Zhou et al, ), while RNA‐binding motif (RBM)‐4, ‐5, RBM single‐stranded interacting protein 3 (RBMS3), and PCBP1 were inhibited (Ji et al, ; Kobayashi et al, ; Y. Wu et al, ; Yong et al, ; T. Zhang et al, ). These aberrant expression patterns were thought to associate with pathologic feature and survival of GC patients, but further investigations are needed to reveal their functions and direct targets during cancer development.…”
Section: Major Functions Of Rbps In Gi Cancermentioning
confidence: 99%
“…HnRNPK fulfills a wide variety of cellular functions, for example by acting as a transcription factor, regulating translation, and serving as a hub for various signaling pathways [141]. Numerous studies have observed oncogenic effects as well as a prognostic relevance of hnRNPK in different types of cancer, like breast, colorectal, and gastric cancer, where its overall levels are increased and it is aberrantly localized in the cytoplasm [142][143][144]. The binding of hnRNPK to RNA occurs via the interaction of its three KH domains, which are a type of RNA-binding motif first discovered in and therefore named after the RBP, with poly-C sequences in the RNA targets [145,146].…”
Section: Heterogeneous Nuclear Ribonucleoprotein K (Hnrnpk)mentioning
confidence: 99%